High‐performance polyimide nanofibers reinforced polyimide nanocomposite films fabricated by co‐electrospinning followed by hot‐pressing. Issue 47 (3rd September 2018) - Xu, W.; Ding, Y.; Huang, R.; Zhu, Z.; Fong, H.; Hou, H.
ABSTRACT: The objective of this study was to develop aligned electrospun polyimide (PI) nanofibers (with rigid macromolecular backbone) reinforced PI (with flexible macromolecular backbone) nanocomposite films. Owing to uniform dispersion of aligned PI nanofibers and excellent interfacial adhesion/interaction between filler and matrix, the resulting nanocomposite films exhibited superior mechanical and thermal properties. The nanocomposite films were fabricated by co‐electrospinning of two polyamic acids (PAAs) including a rigid PAA of poly(p‐phenylene biphenyltetracarboximide) (BPDA‐PDA) and a flexible PAA of poly(1, 4‐bis (3′, 4′‐dicarboxyphenoxy) phenyldiphenyl ether tetramine) (HQDA‐ODA); upon thermal imidization, hybrid PAA nanofiber belts (with different weight ratios of BPDA‐PDA/HQDA‐ODA) were converted into hybrid PI nanofiber belts. Subsequently, these nanofiber belts were hot‐pressed to fabricate HQDA‐ODA PI nanocomposite films reinforced with BPDA‐PDA PI nanofibers; in specific, the nanocomposite film consisting of 80 wt % BP‐PI nanofibers exhibited the highest tensile strength and modulus of 957 ± 18 MPa and 12.32 ± 0.32 GPa, respectively. The nanocomposite films also possessed excellent thermal/thermomechanical properties. Therefore, these fiber‐reinforced PI nanocomposite films might be promising high‐performance structural/engineering materials that would be particularly useful for high‐temperature applications. Moreover, the strategy of co‐electrospinning hybrid nanofiber belts followed by hot‐pressing could provide an innovative approach for making high‐performance polymer‐matrix composites. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46849. Abstract :